2016
DOI: 10.1002/ppap.201600107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Helical and Helicon Antennas as Sources of Plasma Excitation Using a Full Wave 3D Electromagnetic Analysis in Vacuum

Abstract: Helical and Helicon antennas are routinely used to generate inductively coupled plasmas, but there are only a few simulations or experimental data with comparisons among them. Thus, selection of the appropriate number of turns, or the type of helical or helicon antenna to use is empirical. In this paper, a comparison via simulation of various helixes and helicon antennas is presented. Full wave 3D electromagnetic analysis is performed in vacuum using a commercial software, and the electric/magnetic field compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In helicon plasma systems, the coil is coupled to the RF generator through the helical spring-like structure, and a propagating wave (W-mode) helicon plasma is obtained by the effect of the magnetic field (100–300 G) [ 35 ]. A theoretical study to optimize the various antennas as a potential plasma source to produce IC plasma by Gogolides et al stated that, the electric field was scale with the number of loops of the coil for a constant current [ 37 ]. Compared to the ICP systems, a CCP system consists of two parallel plate electrodes, where the electrostatic waves (E-mode) are produced in between these two parallel plate electrodes, which are capacitively coupled to the RF source for the plasma discharge.…”
Section: Plasma: Potential Approach For Carbon Nanowall (Cnw) Syntmentioning
confidence: 99%
“…In helicon plasma systems, the coil is coupled to the RF generator through the helical spring-like structure, and a propagating wave (W-mode) helicon plasma is obtained by the effect of the magnetic field (100–300 G) [ 35 ]. A theoretical study to optimize the various antennas as a potential plasma source to produce IC plasma by Gogolides et al stated that, the electric field was scale with the number of loops of the coil for a constant current [ 37 ]. Compared to the ICP systems, a CCP system consists of two parallel plate electrodes, where the electrostatic waves (E-mode) are produced in between these two parallel plate electrodes, which are capacitively coupled to the RF source for the plasma discharge.…”
Section: Plasma: Potential Approach For Carbon Nanowall (Cnw) Syntmentioning
confidence: 99%
“…In addition, the effects of Faraday shield also been verified in some other experiments, a review and summary of works can be found in Refs. [24, 25].…”
Section: Resultsmentioning
confidence: 99%
“…Later, Boswell and Chen [ 23 ] studied the influence of the use of Faraday shield on plasma density. In the research studies of Stratakos, [ 24,25 ] detailed simulations of the Faraday shielding of a half‐Nagoya antenna and a Nagoya III antenna were carried out using the CST simulation software.…”
Section: Introductionmentioning
confidence: 99%
“…From the real and imaginary parts of the impedance, it was concluded that the single-loop out-performs the other two at low densities, and that the type-III Nagoya behaves better at higher magnetic fields. Stratakos et al [33] used a commercially available fullwave 3-D electromagnetic analysis code (the CST microwave studio) to compare different antenna geometries. Four designs were discussed, that are, the two helical with N = 1 and 4, the half, and the full Nagoya type-III antennas.…”
mentioning
confidence: 99%